Molecular footprint and pathways of DOM biotransformation in the Yangtze River - Guangrui Yang; Farong Chen; Songchol Kang; Jiaming Chen; Chu Zhao; Lize Meng; Xinyi Zhang; Jiayue Lu; Shuaidong Li; Zihao Bian; Jian Zhou; Qihao Jiang; et al. (Water Research, 2026)

Oxidative-stress-mediated apoptosis triggered by microplastics disrupts bovine oocyte maturation - Yu Wang; Jiaming Yue; Yijing Yin; Yan Zhang; Yi Zheng; Hao Jiang; Jiabao Zhang; Bao Yuan; Liang Shuang (Theriogenology, 2026)

LvBlimp1 and LvHes1 coregulate the function of macrophage-like phagocytes in shrimp hemolymph - Jiaming Liu; Yaohui Chen; Wenyong Jiang; Zhiyao Lu; Nuo Lin; Qingyun Liu; Xiuli Chen; Yongzhen Zhao; Fan Wang (Fish & Shellfish Immunology, 2026)

Carbide-induced high dispersion and electronic regulation of Pt species toward stable propane dehydrogenation - Xiaonan Wang; Jiaming Ma; Jun Li; Haoyu Yan; Zhikai Yang; Bo Jiang; Xiao Zhang (Chemical Engineering Journal, 2026)

Electrochemically crosslinked poly(arylene ether sulfone)-triphenylamine electrochromic polymer networks for smart windows - Keying Feng; Zhen Xing; Xiangfu Shi; Jiaming Tian; Hao Zhang; Zong-Quan Wu; Zheng Chen; Zhenhua Jiang (Chemical Engineering Journal, 2026)

Sex-specific differences in cadmium accumulation and responses in the freshwater snail Cipangopaludina cathayensis - Wei Jinyou; Xiang Shanshan; Yu Jing; Li Linli; Tan Haizhen; Ye Quanqing; Yang Liu; Deng Yufan; Cui Jiaming; Wu Zhengjun; Jiang Jiaoyun (Chemico-Biological Interactions, 2026)

Effects of renewable portfolio standards obligation distribution: Equilibrium analysis of supply side vs. demand side in power supply chain networks - Huan Zhang; Jiaming Wu; Sien Chen; Jianli Jiang (Utilities Policy, 2026)

Molecularly functionalized high-Q THz metasurface via q-BIC for selective HbA1c detection - Chang Liu; Min Gao; Zichen Zhang; Junxiao Liu; Ligeng Jin; Xin Tian; Lijun Jiang; Zhongmei Zheng; Chuanyue Li; Jiaming Feng; Xingyu Liao; Zhihang Long; et al. (Chemical Engineering Journal, 2026)

Transport Pathway Evolution and Retention Dynamics of Escherichia Coli in Homogeneous and Heterogeneous Porous Media - Yuanyuan Jia; Zhipeng Tu; Wenjing Zhang; Shutong Jiang; Jiaming Sun; Bo Wan (Transport in Porous Media, 2026)

Freeze–thaw cycles control successive glacier landslide hazards in Amney Machen Mountain - Jiaming Ye; Ruochen Jiang; Shihao Xiao; Yingyue Han; Luyu Ju; Wenjun Lu; Ruiqiang Bai; Tao Yao; Limin Zhang (Landslides, 2026)
Climate change has markedly increased the susceptibility of glacier-related landslides to alpine environments, leading to cascading processes with catastrophic impacts. Nevertheless, their triggering processes remain inadequately understood, which hinder robust hazard assessments and effective risk mitigation. Glacier collapses and cascading processes have been frequently observed at Xiaoma Gully in Amney Machen Mountain. Based on remote sensing, meteorological data analyses, field surveys and numerical simulations, glacier landslide hazard chains in this gully are reconstructed and associated triggers are identified. Results indicate that extreme diurnal freeze–thaw cycles drove the Xiaoma glacier collapses, and extreme temperature and precipitation accelerated glacier instabilities. The 365-day cumulative number of diurnal freeze–thaw cycles is identified as a critical precursor for initiating glacier collapses, serving as a quantitative indicator to characterize the long-term impact of freeze–thaw cycles. The application of this indicator to the Kolka Glacier collapse at Genaldon Valley in Russian Caucasus further demonstrates its feasibility. Furthermore, the catastrophic glacier landslide cascades underwent hazard-type transformation and displayed high mobility, reaching peak flow velocities over 30 m/s. This study sheds light on early warning and emergency management of glacier collapses in alpine regions.

A novel multifunctional bacterial consortium synergistically promotes rhizoremediation of dibutyl phthalate and cucumber growth: Insights from multi-omics analyses - Jiaming Xu; Yan Li; Haoyan Han; Yi Wu; Yue Tao; Yuexuan Ma; Zhao Jiang; Ying Zhang (Journal of Environmental Sciences, 2026)

In-situ sulfur element-induced heterogeneous interface engineering for high-performance supercapacitors - Mingzhe Shan; Yi Jiang; Ruixiang Xu; Bin Cai; Yi Gao; Heju Zhao; Jiaming Wang; Yaozeng Lu; Xiqing Song; Surong Tan; Yishan Yuan; Zining Li; et al. (Chemical Engineering Journal, 2026)

Engineering a Ga-Mn-Zr trimetallic oxide to modulate intermediates for highly selective light olefin synthesis from syngas - Xiuyun Jiang; Songpeng Cheng; Qingxiang Ma; Guangbo Liu; Jinhu Wu; Caixia Zhu; Reubroycharoen Prasert; Jiaming Liang; Xinghua Gao; Yingluo He; Guohui Yang; Noritatsu Tsubaki (Chemical Engineering Journal, 2026)

The dual roles of dissolved organic matter as a source and sink of hydroxyl radicals in the photodegradation of carbamazepine in liquid water and ice - Caihong Jiang; Jiaming Chen; Meng Yuan; Shuang Xue; Yingzi Lin; Yingtan Yu (Process Safety and Environmental Protection, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Circadian Rhythm Disorder-Related Dysfunctions are Exacerbated by Aging and Ameliorated by Time-Restricted Feeding - Fengjiao Huo; Qing Liu; Shuaishuai Zhang; Xiaorui Liu; Shuyao Lv; Meili Zhao; Yue Liu; Xiaoqi Zhu; Ce Huang; Shengyu Feng; Hao Wang; Siling Xu; et al. (Neuroscience Bulletin, 2026)

Impact of Sedimentary Environmental Evolution on Organic Matter Enrichment in Upper Paleozoic Marine-Continental Transitional Shales in the Shenfu Block, Eastern Ordos Basin, China: Evidence from Geochemistry - Yanchao Zhang; Xiangdong Yin; Shu Jiang; Litao Ma; Jiaming Li (Journal of Earth Science, 2026)

Environmental exposure to bisphenol S suppresses white adipocyte beiging and energy expenditure via CYP2E1 in mice - Qi Liu; Yuancheng Shao; Jiaming Xue; Yicheng Jiang; Shuai Chen; Dongmei Wang; Yan Zhou; Jie Zhao; Wei Gao; Liming Tang (Environmental Pollution, 2026)

Localized chemotherapy through metabolic stabilization and in situ gelation for ratio-locked delivery to maximize cytotoxicity and trigger immune responses - Jiaming Zhang; Xinyu Lou; Xiaolan Xu; Yingchao Li; Chenxia Bai; Qing Yan; Yanfang Wang; Yixiu Zhai; Jingdong Xiao; Mengchi Sun; Yinghou Wang; Jin Sun; et al. (Chemical Engineering Journal, 2026)

Integrated network toxicology, molecular docking and transcriptomics reveal the mechanistic role of phthalate esters in metabolic disease pathogenesis - Yuancheng Shao; Qi Liu; Yicheng Jiang; Gang Zhou; Xihan Gu; Shufan Zhang; Shuai Chen; Jiaming Xue; Liming Tang (Food and Chemical Toxicology, 2026)

Targeting Strategies of Stem Cell-Derived Extracellular Vesicles in the Treatment of Cardiovascular Diseases - Jiaming Fan; Liyun Yao; Jiayi Yao; Shumin Jiang; Lianbo Shao; Yunfang Mo; Ziying Yang; Zhenya Shen (Stem Cell Reviews and Reports, 2026)

Extreme precipitation amplified the cumulative effects of DOM availability on organic-sourced DIC in the Yangtze River - Chu Zhao; Guangrui Yang; Lize Meng; Heran Chen; Shuaidong Li; Farong Chen; Zihao Bian; Jiaming Chen; Jian Zhou; Qihao Jiang; Tao Huang; Hao Yang; et al. (Water Research, 2025)

Potential strategies of natural products in the treatment of atherosclerosis: Focusing on modulating macrophage polarization - Wenjie Zhao; Peng Sun; Jiaming Huan; Lei Zhang; Shijing Peng; Tong Jiang; Linghui Kong; Xinghao Zhu; Wenqing Yang; Dongmei Qi; Yunlun Li (PharmaNutrition, 2025)

Lipid-mediated photoprotection confers strong light resilience in hyperaccumulator Sedum alfredii - Yanjiao Dai; Jin Chen; Yang Mao; Huidan Jiang; Wenwen Zhao; Jing Peng; Ruibing Li; Ying Wang; Purui Guo; Mengnan Zhang; Chao Zhang; Jiaming Li; et al. (Plant Science, 2025)

Hybrid fabrication of perfusable stiffness-flexible integrated scaffold mimicking hierarchical tubular bone - Yifan Zhang; Zhipeng Li; Bingkun Bao; Jingyi Ju; Wenbin Jiang; Linyong Zhu; Jiaming Sun; Zhenxing Wang (Chemical Engineering Journal, 2025)

Digital simulation of condensation and water loss in ventilated lychee packaging - Jicheng Lin; Xiaodan Zhang; Yihong Jiang; Dongfeng Liu; Wei Cai; Guopeng Lin; Zhiwu Ding; Enli Lü; Jiaming Guo (Biosystems Engineering, 2025)

Investigation of nTiO2-WTe2 (n = 1–3) nanocluster sensors for the detection of toxic gases H2S, NH3, and NO2 in agricultural greenhouses: A DFT study - Haoming Zhang; Jiaming Jiang; Wen Zhou; Qu Zhou (Journal of Environmental Chemical Engineering, 2025)

Impact of dynamic desiccation cracks on hydrological processes and stability in expansive clay slopes: A coupled dual-permeability modeling approach - Yi Luo; Jiaming Zhang; Chao-Sheng Tang; Guosheng Jiang; Thom Bogaard (Engineering Geology, 2025)

Corrigendum to “Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River” [Sci. Total Environ. 951 (2024) 175535] - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2025)

Exploring the effects of weather-driven dynamics of desiccation cracks on hydrological process of expansive clay slope: Insights from physical model test - Yi Luo; Xinyu Hou; Jiaming Zhang; Yujie Wang; Mingjian Hu; Guosheng Jiang; Chao-Sheng Tang (Journal of Hydrology, 2025)

Differential impacts of rain event and continuous rainfall on biological phosphorus removal of a full-scale wastewater treatment plant: performance analysis and optimization strategies - Jiaming Hu; Lu-Man Jiang; Lihua Wang; Xinya Ding; Xinhong Han; Yan Zhang; Haijuan Wei; Zhan Qiu; Ying An; Zhen Zhou (Journal of Environmental Management, 2025)

Dynamic optimization of cooling temperature setpoints in multiple thermal zones of office buildings in connection with D3QN - Ben Jiang; Jiaming Wang; Yu Li; Peng Wang; Yacine Rezgui; Chengyu Zhang; Menglin Ding; Liuyang Shangguan; Tianyi Zhao (Energy and Buildings, 2025)

Intumescent flame-retardant wood: In situ polymerization of ionic liquids and its mechanism - Jinrui Jiang; Yuzhang Wu; Jiaming Luo; Wei Qu (Chemical Engineering Journal, 2025)

Extraction of Chlorella polysaccharide using natural deep eutectic solvent - Bingfeng Zhou; Jiaming Jiang; Yu Huo; Juying Lin; Huiqing Zhang; Changhua Shang (Algal Research, 2025)

Purification and characterization of cellulase produced by Bacillus sp. HMM - Lanqian Huang; Lei Mo; Jiaming Jiang; Yu Huo; Shisong Yu; Jianmei Ou; Siyu Liu; Xinyu Xie; Guyu Yan; Chuzun Liao; Shangxin Wu; Huiqing Zhang; et al. (Antonie van Leeuwenhoek, 2025)

Extraction, purification and antioxidant activity of Chlorella polysaccharide - Bingfeng Zhou; Jiaming Jiang; Yu Huo; Juying Lin; Changhua Shang (Algal Research, 2025)

A deep learning-based data augmentation method for marine mammal call signals - Jiaming Jiang; Wanlu Cheng; Shengwen Gong; Jingjing Wang (Frontiers in Marine Science, 2025)
In marine ecology research, it is crucial to accurately identify the marine mammal species active in the target area during the current season, which helps researchers understand the behavioral patterns of different species and their ecological environment. However, the difficulty and high cost of collecting marine mammal calls, coupled with limited publicly available datasets, result in insufficient data for support, making it difficult to obtain accurate and reliable identification results. To address this problem, we propose MarGEN, a deep learning-based augmentation method for marine mammal call signal data. This method processed the call data into Mel spectrograms, then designed a self-attention conditional generative adversarial network to generate new samples of Mel spectrograms that were highly similar to the real data, and finally reconstructed them into call signals using WaveGlow. The classification experiments on the calls of four Marine mammals show that MarGEN significantly enriches the diversity and volume of the data, increasing the classification accuracy of the model by an average of 4.7%. The method proposed in this paper greatly promotes marine ecological protection and sustainable development, while effectively advancing research progress in bionic covert underwater acoustic communication technology.

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Recognition and classification techniques of marine mammal calls based on LSTM and expanded causal convolution - Wanlu Cheng; Hao Chen; Jiaming Jiang; Shuang Li; Jingjing Wang; Yanping Zhou (Frontiers in Marine Science, 2025)
Marine mammal calls play a vital role in navigation, localization, and communication. Effectively classifying these calls is essential for ecological monitoring, species conservation, and military biomimetic applications. However, traditional machine learning methods struggle to capture complex acoustic patterns, while most existing deep learning approaches rely solely on frequency-domain features and require large datasets, which limits their performance on small-scale marine mammal datasets. To address these challenges, we propose a hybrid architecture combining a time-attention Long Short-Term Memory (LSTM) network and a multi-scale dilated causal convolutional network. The model comprises three modules: (1) a frequency-domain feature extraction module employing dilated causal convolutions at multiple scales to capture multi-resolution spectral information from Mel spectrograms; (2) a time-domain feature extraction module that inputs Mel-frequency cepstral coefficients (MFCCs) into an LSTM enhanced with a time-attention mechanism to highlight key temporal features; and (3) a classification module leveraging transfer learning, where a pre-trained neural network is fine-tuned on real marine mammal call data to improve performance. Extensive experiments were conducted on vocalizations from four marine mammal species. Our proposed method outperformed existing baseline models across four evaluation metrics: accuracy, precision, recall, and F1 score, with improvements of 3%, 7%, 2%, and 4%, respectively. The results confirm the effectiveness of combining frequency- and time-domain features along with attention mechanisms and transfer learning. This hybrid approach enhances the accuracy and robustness of marine mammal call classification, especially under limited data conditions.

Effects of chlorpyrifos stress on the Eriocheir sinensis suffering from Metschnikowia bicuspidata infection - Jiaming Dong; Yuanyuan Tan; Chengcheng Feng; Qingbiao Hu; Yanhong Zhao; Jie Bao; Hongbo Jiang (Aquaculture, 2025)

Multi-omics revealed activation of TNF-α induced apoptosis signaling pathway in testis of DEHP treated prepubertal male rat - Zishui Fang; Zirun Jin; Qiancheng Zhao; Jiaming Weng; Zhe Zhang; Yuzhuo Yang; Hui Jiang (Reproductive Toxicology, 2025)

Kill two birds with one stone: Biochar immobilised polydopamine coated compound bacterial agent for remediation of dibutyl phthalate contaminated soil - Yue Tao; Jiaming Xu; Ang Li; Zhao Jiang; Ningyuan Ma; Rui Sun; Ying Zhang (Environmental Research, 2025)

Chronic chlorpyrifos exposure induces oxidative stress, neurological damage, and hepatopancreas enrichment in Chinese mitten crab (Eriocheir sinensis) - Yuanyuan Tan; Jiaming Dong; Luyao Wang; Weining Li; Jie Bao; Hongbo Jiang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Efficient extraction of Spirulina phycocyanin using natural deep eutectic solvents and its characteristics - Juying Lin; Jiaming Jiang; Lei Mo; Yu Huo; Yan Pang; Bingfeng Zhou; Changhua Shang (Algal Research, 2025)

Achieving remarkable charge transfer through the depolarization field in the 2D/2D S-scheme heterojunction consisted of C3N5 nanosheets and layered ferroelectric Bi3TiNbO9 for photocatalytic hydrogen production - Haotian Guo; Jinhui Jiang; Jiaming Liang; Chunyang Wen; Xinguo Xi; Pengyu Dong (Chemical Engineering Journal, 2025)

Mapping QTLs for stigma exsertion-related traits in two sets of CSSL populations of Oryza sativa cultivars using RSTEP-LRT method - Chunyu Jing; Mei Hai; Jiaming Shen; Xinru Li; Mengyuan Zhang; Changmin Hu; Qing Xu; Jianhua Jiang; Xiaojing Dang (Euphytica, 2025)

Extraction, purification and characterization of Spirulina phycocyanin - Juying Lin; Yan Pang; Yu Huo; Jiaming Jiang; Bingfeng Zhou; Changhua Shang (Algal Research, 2025)

Electroactive supramolecular nanoprobes for electrochemical detection of rituximab in non-Hodgkon’s lymphoma patients - Zhiwei Chen; Zheng Zhao; Jiaming Yuan; Qiaoxuan Zhang; Yufeng Wu; Qingjin Wu; Yuheng Liao; Jia-Huan Qu; Ning Gan; Zhengjin Jiang; Qiqin Wang (Chemical Engineering Journal, 2024)

Whole genome sequencing and analysis of Bacillus sp. TTMP2, a tetramethylpyrazine-producing bacterium - Shanling Gan; Lingru Ruan; Xinyi Xu; Lirong Luo; Yu Huo; Jiaming Jiang; Xiumin Zhang; Changhua Shang (Molecular Biology Reports, 2024)

Spatial Patterns and Drivers of Intelligent Manufacturing from a ‘Global-local’ Perspective: A Study of China’s Industrial Robotics - Fengjiao Li; Hong Zhang; Lili Jiang; Jiaming Liu (Chinese Geographical Science, 2024)

Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2024)

Innovative approach to enhancing phosphogypsum mechanical properties and stabilizing/solidifying contaminants - Lina Xiao; Jiaming Zhang; Yi Luo; Xiaojian Qi; Javid Hussain; Guosheng Jiang (Sustainable Chemistry and Pharmacy, 2024)

The involvement of tumor necrosis factor receptor-associated factor 6 in regulating immune response by NF-κB at pre-molt stage of Chinese mitten crab (Eriocheir sinensis) - Jialin Li; Yuhan Ma; Zihao Wu; Jiaming Li; Fengchi Wang; Zhichao Yang; Yuting Xi; Dazuo Yang; Yusheng Jiang; Qilin Yi; Shu Huang (Fish & Shellfish Immunology, 2024)

Multiple synergistic antibacterial melamine-impregnated paper based on nano Ag-doped ZIF-8 - Jinrong He; Wei Qu; Yun Feng; Jinrui Jiang; Jiaming Luo; Yuzhang Wu; Limin Peng (Chemical Engineering Journal, 2024)

Hydrocarbon Source and Relationship between Hydrocarbon Charging Process and Reservoir Tight Period of the Denglouku Formation Tight Sandstone Gas Reservoirs in the Xujiaweizi Fault Depression, Songliao Basin - Huan Miao; Zhenxue Jiang; Jiaming Lu; Chengju Zhang; Lidong Shi; Lidong Sun; Liang Yang; Peng Shang (Natural Resources Research, 2024)

Development of a water gradient film through film and ice-glazing approach utilizing konjac glucomannan and high acyl gellan gum for enhanced preservation of frozen snakehead (Channa argus) fillets - Man Xiao; Chun Peng; Jiaming Qin; Shuangshuang Wang; Xiaohe Wu; Katsuyoshi Nishinari; Fatang Jiang (Food Hydrocolloids, 2024)

Cryopreserved leukapheresis material can be transferred from controlled rate freezers to ultracold storage at warmer temperatures without affecting downstream CAR-T cell culture performance and in-vitro functionality - Jiaming Wei; Katherine Chaney; Woo Jin Shim; Heyu Chen; Grace Leonard; Sean O'Brien; Ziyan Liu; Jinlin Jiang; Robert Ulrey (Cryobiology, 2024)

Alterations in Dynamic Functional Connectivity in Patients with Cerebral Small Vessel Disease - Futao Chen; Qian Chen; Yajing Zhu; Cong Long; Jiaming Lu; Yaoxian Jiang; Xin Zhang; Bing Zhang (Translational Stroke Research, 2024)
Cerebral small vessel disease (CSVD) is a common disease that seriously endangers people’s health, and is easily overlooked by both patients and clinicians due to its near-silent onset. Dynamic functional connectivity (DFC) is a new concept focusing on the dynamic features and patterns of brain networks that represents a powerful tool for gaining novel insight into neurological diseases. To assess alterations in DFC in CSVD patients, and the correlation of DFC with cognitive function. We enrolled 35 CSVD patients and 31 normal control subjects (NC). Resting-state functional MRI (rs-fMRI) with a sliding-window approach and k -means clustering based on independent component analysis (ICA) was used to evaluate DFC. The temporal properties of fractional windows and the mean dwell time in each state, as well as the number of transitions between each pair of DFC states, were calculated. Additionally, we assessed the functional connectivity (FC) strength of the dynamic states and the associations of altered neuroimaging measures with cognitive performance. A dynamic analysis of all included subjects suggested four distinct functional connectivity states. Compared with the NC group, the CSVD group had more fractional windows and longer mean dwell times in state 4 characterized by sparse FC both inter-network and intra-networks. Additionally, the CSVD group had a reduced number of windows and shorter mean dwell times compared to the NC group in state 3 characterized by highly positive FC between the somatomotor and visual networks, and negative FC in the basal ganglia and somatomotor and visual networks. The number of transitions between state 2 and state 3 and between state 3 and state 4 was significantly reduced in the CSVD group compared to the NC group. Moreover, there was a significant difference in the FC strength between the two groups, and the altered temporal properties of DFC were significantly related to cognitive performance. Our study indicated that CSVD is characterized by altered temporal properties in DFC that may be sensitive neuroimaging biomarkers for early disease identification. Further study of DFC alterations could help us to better understand the progressive dysfunction of networks in CSVD patients.

Effects of improper emergency mitigations on a large-scale landslide triggered by road excavation: A case study of the Fengping landslide, Hubei province, China - Yi Luo; Jiaming Zhang; Zhi Zhou; Guosheng Jiang; Modong Duan (Bulletin of Engineering Geology and the Environment, 2024)

Effect of temperature on the occurrence of Metschnikowia bicuspidata disease in Eriocheir sinensis - Hongbo Jiang; Gangnan Cao; Jie Bao; Chengcheng Feng; Xiaodong Li; Yuanyuan Tan; Jiaming Dong; Qijun Chen (Aquaculture, 2024)

Biochar reduces gaseous emissions during poultry manure composting: Evidence from the evolution of associated functional genes - Ruijing Dang; Yu Cai; Jiaming Li; Yilin Kong; Tao Jiang; Jiali Chang; Sheng Yao; Jing Yuan; Guoxue Li; Guoying Wang (Journal of Cleaner Production, 2024)

Molecular Determinants of Neurocognitive Deficits in Glioma: Based on 2021 WHO Classification - Kun Zhang; Tianrui Yang; Yu Xia; Xiaopeng Guo; Wenlin Chen; Lijun Wang; Junlin Li; Jiaming Wu; Zhiyuan Xiao; Xin Zhang; Wenwen Jiang; Dongrui Xu; et al. (Journal of Molecular Neuroscience, 2024)
Cognitive impairment is a common feature among patients with diffuse glioma. The objective of the study is to investigate the relationship between preoperative cognitive function and clinical as well as molecular factors, firstly based on the new 2021 World Health Organization’s updated classification of central nervous system tumors. A total of 110 diffuse glioma patients enrolled underwent preoperative cognitive assessments using the Mini-Mental State Examination and Montreal Cognitive Assessment. Clinical information was collected from medical records, and gene sequencing was performed to analyze the 18 most influenced genes. The differences in cognitive function between patients with and without glioblastoma were compared under both the 2016 and 2021 WHO classification of tumors of the central nervous system to assess their effect of differentiation on cognition. The study found that age, tumor location, and glioblastoma had significant differences in cognitive function. Several genetic alterations were significantly correlated with cognition. Especially, IDH , CIC , and ATRX are positively correlated with several cognitive domains, while most other genes are negatively correlated. For most focused genes, patients with a low number of genetic alterations tended to have better cognitive function. Our study suggested that, in addition to clinical characteristics such as age, histological type, and tumor location, molecular characteristics play a crucial role in cognitive function. Further research into the mechanisms by which tumors affect brain function is expected to enhance the quality of life for glioma patients. This study highlights the importance of considering both clinical and molecular factors in the management of glioma patients to improve cognitive outcomes.

FRPNet: An improved Faster-ResNet with PASPP for real-time semantic segmentation in the unstructured field scene - Biao Yang; Sen Yang; Peng Wang; Hai Wang; Jiaming Jiang; Rongrong Ni; Changchun Yang (Computers and Electronics in Agriculture, 2024)

Characteristics and multi-factor mechanisms of dam construction on food web structure in cold-region rivers - Jiaming Hou; Qinghui Zeng; Peng Hu; Yunzhong Jiang; Yinglan A; Qin Yang; Baolong Zhao; Huan Liu; Zefan Yang; Xiaohui Qu (Journal of Hydrology, 2024)

A new strategy for self-bio-driven granular sludge in a continuous-flow reactor: Applying spherical pelletizing granular sludge as a nucleus - Zhuo Sun; Libin Zhang; Xuejiao Huang; Zhongqin Jiang; Jin Wang; Hongxiang Zhu; Jianhua Xiong; Jiaming Zhang; Dandan Jia (Journal of Cleaner Production, 2024)

Visible-light photocatalytic degradation of water-soluble polyvinyl alcohol in aqueous solution by Cu2O@TiO2: Optimization of conditions, mechanisms and toxicity analysis - Jiaming Zhang; Zhenqi Zhou; Bing Xiao; Chenxu Zhou; Zhongqin Jiang; Yinna Liang; Zhuo Sun; Jianhua Xiong; Guoning Chen; Hongxiang Zhu; Shuangfei Wang (Journal of Environmental Management, 2023)

CRISPR-Cas12a powered multifunctional DNA nanodumbbell lock biosensor for multiple molecular detection - Yuqing Zhu; Xiaohe Zheng; Rui Zhu; Hongrui Zhao; Hongli Zhai; Feiyang Qian; Tenghua Zhang; Zihui Xie; Silan Liu; Bowen Jiang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2023)

FOXO-like Gene Is Involved in the Regulation of 20E Pathway through mTOR in Eriocheir sinensis - Jiaming Li; Yuhan Ma; Zhichao Yang; Fengchi Wang; Jialin Li; Yusheng Jiang; Dazuo Yang; Qilin Yi; Shu Huang (Journal of Marine Science and Engineering, 2023)
The Forkhead Box O (FOXO) gene plays a key role in various biological processes, such as growth, metabolism, development, immunity and longevity. Molting is an essential process for crustacean growth, which is mainly regulated by 20-hydroxyecdysone (20E) and molt-inhibiting hormone (MIH). Although the role of FOXO in regulating the immune response of crustaceans is well documented, its involvement in controlling crustacean molting remains unclear. In this study, a FOXO-like gene (designed as EsFOXO-like) was identified in Eriocheir sinensis, and the regulation of the 20E pathway by EsFOXO-like was also investigated. The coding sequence of EsFOXO-like was 852 bp, which consisted of 283 amino acids including a conserved Forkhead (FH) domain. EsFOXO-like shared high similarity with FOXO genes from other crustaceans, and the mRNA expression levels of the EsFOXO-like gene were highest in the hepatopancreas and lowest in the hemocytes. However, transcription and protein expression of the EsFOXO-like gene were found to be up-regulated only during the pre-molt stage in the hepatopancreas, with lower expression levels observed at the post-molt stage. To explore the role of EsFOXO-like in the 20E pathway, EsFOXO-like was firstly inhibited by a specific FOXO inhibitor (AS1842856) and then through an EsFOXO-like dsRNA injection, respectively, and the results showed that the relative expression levels of EsFOXO-like were notably decreased in the hepatopancreas after both the inhibitor and dsRNA treatments. The 20E concentration, the mRNA expression levels of the 20E receptors including the ecdysone receptor (EcR) and the retinoid-X receptor (RXR) and EsmTOR transcription in the AS1842856 group or the EsFOXO-RNAi group were all significantly higher than that in the control group, while the mRNA expression level of EsMIH was significantly decreased after EsFOXO-like inhibition. To further investigate whether the EsFOXO-like acts through mTOR or not, Rapamycin was administered to inhibit mTOR activity in EsFOXO-like inhibited crabs. The results revealed a significant reduction in the concentration of 20E and the expression level of EsMIH in the AS1842856 + Rapamycin group compared to the AS1842856 + DMSO group, accompanied by an increase in EsEcR and EsRXR expression. These findings collectively suggest that EsFOXO-like regulates the 20E pathway through mTOR, which offered valuable insights into the understanding of the molting process in crustaceans.

Detection and characterization of microplastics in the human testis and semen - Qiancheng Zhao; Long Zhu; Jiaming Weng; Zirun Jin; Yalei Cao; Hui Jiang; Zhe Zhang (Science of The Total Environment, 2023)

Effects of carboxymethyl cellulose on the emulsifying, gel and digestive properties of myofibrillar protein-soybean oil emulsion - Lei Zhou; Jinyuan Jiang; Fan Feng; Jingyu Wang; Jiaming Cai; Lujuan Xing; Guanghong Zhou; Wangang Zhang (Carbohydrate Polymers, 2023)

MLKL and other necroptosis-related genes promote the tumor immune cell infiltration, guiding for the administration of immunotherapy in bladder urothelial carcinoma - Boqiang Zhong; Youzhi Wang; Yihao Liao; Jiaming Liang; Keke Wang; Diansheng Zhou; Yang Zhao; Ning Jiang (Apoptosis, 2023)
The involvement of necroptosis in the immunosuppressive tumor microenvironment has been established and has been shown to contribute to the growth of pancreatic ductal adenocarcinoma, indicating its role in promoting tumor development. However, the relationship between necroptosis and bladder urothelial carcinoma (BUC) has yet to be fully understood. To shed light on this issue, our study aimed to uncover the impact of necroptosis on immune cell infiltration and immunotherapy response in BUC patients. We conducted an analysis of 67 necroptosis genes to assess their expression and genomic changes across pan-cancer and identified 12 necroptosis genes that are prognostically relevant and associated with immune subtypes and tumor stemness in BUC. Using a public database of 1841 BUC samples, we then performed Unsupervised Cluster Analysis and discovered two distinct necroptotic phenotypes in BUC. These phenotypes showed significant differences in molecular subtypes, immune infiltration patterns, and gene mutation profiles. We confirmed this discovery in BUC through qPCR and WB experiments. To evaluate the impact of necroptosis on prognosis, chemotherapy sensitivity, and immunotherapy response (such as anti-PD-L1), we developed a principal component analysis model called NecroScore. Finally, we validated the effects of RIPK3 and MLKL through a nude mouse transplantation model for BUC. Our study has uncovered that necroptosis plays a role in shaping the tumor immune microenvironment in BUC. The high necroptosis phenotype (Cluster B) was characterized by a higher abundance of tumor immunosuppressive cells and more key biological processes driving tumor progression, while the low necroptosis group (Cluster A) had higher FGFR3 mutations. We found that the infiltration levels of immune cells, including CD8+ T cells, were significantly different between FGFR3 mutated and wild-type (WT) samples. Our results confirmed the reliability of NecroScore as a comprehensive assessment tool for evaluating the immunotherapeutic effect and prognosis of BUC patients, with high NecroScore values favoring basal-like differentiation and lower FGFR3 alterations. We also observed that high expression of MLKL had a significant inhibitory effect on tumor growth and increased neutrophil infiltration in vivo. In our study, we uncovered the regulation pattern of necroptosis in the tumor immune microenvironment of BUC. Additionally, we developed a scoring tool called NecroScore that can be utilized to predict the most suitable chemotherapy and immunotherapy strategy for bladder urothelial carcinoma patients. This tool can effectively guide the chemotherapy and immunotherapy regimens for patients with advanced BUC.

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Genomic Profiling of Lower-Grade Gliomas Subtype with Distinct Molecular and Clinicopathologic Characteristics via Altered DNA-Damage Repair Features - Aierpati Maimaiti; Yanwen Liu; Aimitaji Abulaiti; Xixian Wang; Zhaohai Feng; Jiaming Wang; Maimaitili Mijiti; Mirzat Turhon; Nilipaer Alimu; Yongxin Wang; Wenbao Liang; Lei Jiang; et al. (Journal of Molecular Neuroscience, 2023)

Correction to: Modulating red mud for the fabrication of cementitious material by analyzing the thermal evolution of hydrogarnets - Beibei Wang; Jiaming Wu; Xiaojie Sun; Jun Jiang; Qingchun Yang; Quanliang Li; Zhengmao Ye; Jiayu Guo; Xiaohao Wang (Environmental Science and Pollution Research, 2023)

Modulating red mud for the fabrication of cementitious material by analyzing the thermal evolution of hydrogarnets - Beibei Wang; Jiaming Wu; Xiaojie Sun; Jun Jiang; Qingchun Yang; Quanliang Li; Zhengmao Ye; Jiayu Guo; Xiaohao Wang (Environmental Science and Pollution Research, 2023)

Fracture behavior investigation of self-compacting rubberized concrete by DIC and mesoscale modeling - Xing Li; Fuheng Ma; Xudong Chen; Jiang Hu; Jiaming Wang (Journal of Cleaner Production, 2023)

TP-DDI: A Two-Pathway Deep Neural Network for Drug–Drug Interaction Prediction - Jiang Xie; Chang Zhao; Jiaming Ouyang; Hongjian He; Dingkai Huang; Mengjiao Liu; Jiao Wang; Wenjun Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2022)

HIV Tat Protein Induces Myocardial Fibrosis Through TGF-β1-CTGF Signaling Cascade: A Potential Mechanism of HIV Infection-Related Cardiac Manifestations - Yannan Jiang; Lu Chai; Hongguang Wang; Xiuyun Shen; Moyondafoluwa Blessing Fasae; Jinfeng Jiao; Yahan Yu; Jiaming Ju; Bing Liu; Yunlong Bai (Cardiovascular Toxicology, 2021)

Preliminary marine gravity field from HY-2A/GM altimeter data - Qiankun Liu; Ke Xu; Maofei Jiang; Jiaming Wang (Acta Oceanologica Sinica, 2020)

Dynamic Analysis of the Rock Burst Potential of a Longwall Panel Intersecting with a Fault - Lishuai Jiang; Peng Kong; Peipeng Zhang; Jiaming Shu; Qingbiao Wang; Lianjun Chen; Quanlin Wu (Rock Mechanics and Rock Engineering, 2020)

Effect of Fracture Heterogeneity on Rock Mass Stability in a Highly Heterogeneous Underground Roadway - Peng Kong; Lishuai Jiang; Jiaming Shu; Atsushi Sainoki; Qingbiao Wang (Rock Mechanics and Rock Engineering, 2019)

Numerical Analysis of Support Designs Based on a Case Study of a Longwall Entry - Lishuai Jiang; Peng Kong; Jiaming Shu; Kegong Fan (Rock Mechanics and Rock Engineering, 2019)

Alleviation of atrazine toxicity to maize seedlings grown in soils with amendment of biochar derived from wheat under different temperatures - Yifan Wang; Yi Tang; Qun Jiang; Xinyuan Zhang; Weiling Xie; Ruizhen Li; Wenzhu Liu; Jiaming Kang; Ying Zhang (Environmental Science and Pollution Research, 2019)

Soil heavy metal contamination related to roasted stone coal slag: a study based on geostatistical and multivariate analyses - De’an Li; Jianguo Jiang; Tianran Li; Jiaming Wang (Environmental Science and Pollution Research, 2016)

Removal of Pb and Zn from contaminated soil by different washing methods: the influence of reagents and ultrasound - Jiaming Wang; Jianguo Jiang; Dean Li; Tianran Li; Kaimin Li; Sicong Tian (Environmental Science and Pollution Research, 2015)

Characterization of transcriptional activation and inserted-into-gene preference of various transposable elements in the Brassica species - Caihua Gao; Meili Xiao; Lingyan Jiang; Jiana Li; Jiaming Yin; Xiaodong Ren; Wei Qian; Ortegón Oscar; Donghui Fu; Zhanglin Tang (Molecular Biology Reports, 2012)